Visualización de conocimiento en temas específicos mediante el uso del correo electrónico corporativo - Alvarado-Brenes, Berny (Instituto Tecnológico de Costa Rica., 2014)
Understanding who within a corporation has knowledge on a given topic, is key for effective decision making that enables the best use of the resources and strengthens collaboration. Based on studies of social network analysis, information visualization techniques are evaluated, the most adequate visualization is selected, and improvements developed over it.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2014.
Keywords: Infoesfera; Teléfonos celulares; Extracción de datos; Outlook; Formato MIME